Triticum durum, Triticum dicoccum, general combining ability, specific combining ability, non-additive gene effects. - DESAI, S.A.; LOHITHASWA, H.C.; HANCHINAL, R.R.; PATIL, B.N.; MATH, K.K.; KALAPPANAVAR, I.K. (Annals of Agricultural Research, 2014)
Combining ability for grain yield per plant and its components, quality traits and rust resistance was studied using five lines and seven testers and 35 crosses produced in LXT mating system in durum and emmer wheat. Analysis of variance for combining ability revealed that variance due to females, males and female x male was significant for all the traits studied. The general and specific combining ability variance ratio revealed the preponderance of non-additive gene action for all the traits. Significant gca effects for grain yield and its component traits was exhibited by the lines Vijay and DK-1001 and testers DWR-1006 and Raj-1555. Fourteen crosses recorded significant sea effects for grain yield and related traits.